RANCANGAN HANDOUT BIOLOGI PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN PADA TUMBUHAN UNTUK SMA KELAS XII - Anisa Fitriyana; Zulfarina Zulfarina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to produce a handout design for high school biology class XII on growth and development in plants. The research was conducted at FKIP Riau University in November - January 2022. The design of this handout refers to the ADDIE design model which in this research was carried out until the development stage. At the analysis stage, an analysis of the 2013 revised 2018 curriculum was carried out and an analysis of learning materials. The design stage is done by designing learning tools and designing handouts. The design stage is done by designing a syllabus, lesson plans, and handout design consisting of cover, introduction, table of contents, study instructions, (KI, KD, and GPA), introduction, description of the main material, evaluation, and reference sources. This study aims to design biology handouts for class XII KD SMA. 3.1 and 4.1 on the material of growth and development in plants, especially the factors that affect the growth and development of chili seedlings by utilizing phosphate solubilizing bacteria.Key Words: Handout, Learning Media, Chili Seed Growth